2009
DOI: 10.1093/abbs/gmp041
|View full text |Cite
|
Sign up to set email alerts
|

cDNA microarray reveals the alterations of cytoskeleton-related genes in osteoblast under high magneto-gravitational environment

Abstract: The diamagnetic levitation as a novel ground-based model for simulating a reduced gravity environment has been widely applied in many fields. In this study, a special designed superconducting magnet, which can produce three apparent gravity levels (0, 1, and 2 g), namely high magneto-gravitational environment (HMGE), was used to simulate space gravity environment. The effects of HMGE on osteoblast gene expression profile were investigated by microarray. Genes sensitive to diamagnetic levitation environment (0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 35 publications
3
28
0
1
Order By: Relevance
“…This result also supports a previous study (Qian et al, 2009), thus verifying the accuracy of the present study. Furthermore, we here identified the differentially expressed THFRSF1B, ESRRB, COL10A1, IBSP, TNFRSF11A, and WNT4 genes as potential key genes of osteoporosis.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This result also supports a previous study (Qian et al, 2009), thus verifying the accuracy of the present study. Furthermore, we here identified the differentially expressed THFRSF1B, ESRRB, COL10A1, IBSP, TNFRSF11A, and WNT4 genes as potential key genes of osteoporosis.…”
Section: Resultssupporting
confidence: 94%
“…Cell death had previously been shown to be related to osteoporosis (Bonewald, 2004), as mentioned above. The cytoskeleton is the bracing structure of the cell, and recent research has revealed that changes in the expression of cytoskeleton-related genes are closely associated with bone loss and osteoporosis (Qian et al, 2009).…”
Section: Screening Analysis Of Hub Proteinsmentioning
confidence: 99%
“…Our previous studies have shown that diamagnetic levitation caused by large gradient high superconducting magnet influences cytoskeleton arrangement and expression of associated genes in osteoblast-like and osteocyte-like cells (Qian et al 2008(Qian et al , 2009(Qian et al , 2010. In this study, 48 h of clinorotation, but not 12 h and 24 h of clinorotation, destroyed stress fibre formation and α-tubulin distribution in MLO-Y4 cells.…”
Section: Discussionmentioning
confidence: 45%
“…Both the height and roughness of cytoskeleton are attenuated (Qian et al 2010). Cytoskeleton-associated proteins are found to present altered expression in osteoblasts after being treated in HMGE, as seen in cDNA microarray analysis (Qian et al 2009a). The distributions of actin-binding proteins (vinculin, paxillin, zyxin, and talin) are dispersed and the expressions are also reduced consistently (Nabavia et al 2011;Qian et al 2012).…”
Section: Mechanotransduction Of Bone and Immune Cells Under Microgravitymentioning
confidence: 96%